THE NECESSITY OF PRODUCING A HIGH-QUALITY TRANSLATION OF CAPTIONS IN RADYA PUSTAKA MUSEUM - Dyah Ayu Nila Khrisna; Ida Kusuma Dewi; Bayu Budiharjo (Prasasti: Journal of Linguistics, 2021)
Most information about the Radya Pustaka Museum collection is often provided in the form of captions and storylines. Unfortunately, the Radya Pustaka Museum does not have a proper English version of the captions and storylines to display to its foreign visitors, who played a key role in providing them with important details of its masterpiece collection. In fact, the Radya Pustaka Museum has some captions written in peculiar English phrases that foreign visitors could hardly understand. The process of internationalization of the Radya Pustaka Museum through the availability of information in English is therefore critical. Also, the need to produce high-quality translations should be obvious to achieve optimum communication with tourists, particularly foreign visitors. Accordingly, a translation training and assistance program for the museum staff focuses on the errors that can be made in writing and translating museum storylines, and how they can be fixed is crucial to conduct.